Analysis of Marketing Strategies to Increase Sales of Building Materials at UD Tokosa West Nias District - Lahagu, Alfonsus Indra Baru; Laia, Otanius; Mendrofa, Yupiter; Zalukhu, Yuterlin (ProBisnis : Jurnal Manajemen, 2024)
This research aims to analyze the marketing strategies implemented by UD. Tokosa, a trading business engaged in the sale of building tools in West Nias Regency. The main focus of the research is to understand the effectiveness of marketing strategies that have been applied to increase the sales of building tool products. The research method used involves interviews with business owners, direct observation of marketing activities, and sales data analysis. The data obtained is analyzed using a qualitative approach. Qualitative analysis is used to understand the business owner's perception of the marketing strategies that have been implemented. The results of the research show that UD. Tokosa has implemented various marketing strategies, including promotion through social media, discounts, and collaboration with suppliers. However, sales data analysis indicates significant variations in achieving sales targets. Therefore, this research provides recommendations for improving marketing strategies that can help UD. Tokosa improve the sales performance of building tools, such as increasing online visibility, diversifying promotions, and improving customer service. Thus, this research provides in-depth insights into marketing strategy practices in small and medium-sized businesses in the building tools sector, contributing to business owners and researchers interested in the development of effective marketing strategies. The objectives of this research are to find out what marketing strategies are employed by UD Tokosa in West Nias Regency, to identify factors influencing the sales level, and to analyze marketing strategies in increasing the sales of building tools at UD Tokosa in West Nias Regency.